Post-thinning Responses of Microbial Substrate Utilization in Temperate Japanese Larch Forests. (19th May 2021) - Kim, Seongjun; Li, Guanlin; An, Jiae; Kim, Choonsig; Lee, Sang-Tae; Han, Seung Hyun; Son, Yowhan
ABSTRACT: The present study examined microbial substrate utilization by community level physiological profiling and carbon-cycling enzyme assays (cellobiohydrolase, β-xylosidase, and oxidases) in three Japanese larch forests. The forests differed in their locations, topographies, and soil microclimates, and each covered three treatments, namely 20 (IT) and 35% basal area thinning (HT) without intensive residue harvests and an un-thinned control (UTC). Microbial substrate utilization and soil properties (temperature, moisture, total carbon and nitrogen, inorganic nitrogen, and pH) were analyzed at 0–10 cm depth, six years after thinning. Microbial utilization of carbohydrate group under IT was 27 and 62% higher than that under UTC and HT, respectively, in only one of the forests. This might occur because this forest featured a steeper slope, rockier soil texture, and cooler and drier soil surface than the other two forests, where no thinning effect was observed. However, neither microbial utilization of any other substrate groups nor enzyme activity changed by thinning across all forests. It could result from the exclusion of intensive residue harvests or the lack of changes in soil inorganic nitrogen and pH. These results indicate that the thinning effects on microbial substrate utilization might be inconsistent across multiple sites, and at least, not decline the associated forest ecosystem functions and sustainability.